GRAPHICAL COMPUTING FOR BATIK PATTERN DESIGN BASED ON L-SYSTEM - Hidayat, Eka Wahyu; Anshary, Muhammad Adi Khairul; Nur Shofa, Rahmi (Jurnal Teknik Informatika (Jutif), 2024)
The challenge faced by the batik industry in the industrial era 5.0 is the adaptation to technology in the production process. One way to overcome this challenge is to start from the basics in the batik industry, namely the creative process of designing batik patterns. It is important to pay special attention to this process to enhance digital transformation in the batik industry. The purpose of this paper is to present the design and creation of batik patterns using the L-System-based fractal approach. Previous research has shown that the L-System can be used to model plant growth in 2D and 3D contexts. In a similar way, the L-System is used in this study to create batik patterns. Experiments were conducted through three stages, namely Data Acquisition, Data Identification, and Modeling. The experiment results in a dataset of batik motifs that can be used as parameters to replace line segments in the L-System. The design and creation of batik patterns using the L-System only needs to be done once, so that from one pattern, a variety of different motifs can be produced easily by simply changing the parameters. This shows that the design and creation of batik patterns using L-System is more efficient and practical. In addition, the fractal dimension calculation is used to understand and describe the fractal properties of the resulting objects. In this study, it was found that there are four motifs without ornaments that have higher fractal dimension values than motifs with equivalent ornaments.